Mindless: why smarter machines are making dumber humans - Head, Simon (New York, 2014)
"We live in the age of Computer Business Systems (CBSs)—the highly complex, computer-intensive management programs on which large organizations increasingly rely. In Mindless, Simon Head argues that these systems have come to trump human expertise, dictating the goals and strategies of a wide array of businesses, and de-skilling the jobs of middle class workers in the process. CBSs are especially dysfunctional, Head argues, when they apply their disembodied expertise to transactions between humans, as in health care, education, customer relations, and human resources management. And yet there are industries with more human approaches, as Head illustrates with specific examples, whose lead we must follow and extend to the mainstream American economy. Mindless illustrates the shortcomings of CBS, providing an in-depth and disturbing look at how human dignity is slipping as we become cogs on a white collar assembly line. "